Effect of surface attrition on the microstructure and wear properties of boronized grade 304 stainless steel / Siti Khadijah Alias - Alias, Siti Khadijah (Institute of Graduate Studies, UiTM, 2017)
Grade 304 stainless steel has an excellent strength to weight ratio and high corrosion resistance; unfortunately it possesses very poor wear resistance. The structure of this type of stainless steel is austenitic and cannot be heat treated. This study focused on the effect of surface attrition using the shot blasting method on the surface of boronized grade 304 stainless steel. Boronizing was conducted at temperatures of 850˚C and 950˚C under two types of mediums which were powder and paste for the duration of 8 hours holding time. Boronized samples with thicker boride layer and superior wear properties were thus selected to undergo surface attrition using shot blasting method. The microstructure analysis and boride layer thickness were observed using optical microscopy, scanning electron microscopy (SEM) analyzer and energy dispersive X-Ray (EDX) spectrometry. Other tests such as pin on disc, erosion, microhardness, surface roughness and density were also conducted…